The Role of Musyrif in Improving the Discipline of Santri in the Pesantren Environment - M. Munif; Mustajib (Center for Studies in Advanced Science, 2025)
This study aims to analyze the roles of musyrif (dormitory supervisors) in improving students’ discipline at Ma’had Al Ummah Pandanwangi Jombang. The research employed a descriptive qualitative approach with the primary data sources being musyrif and students (santri), and secondary data obtained from relevant documents. Data were collected through semi-structured interviews, participatory observation, and documentation. Thematic analysis was conducted using the Miles, Huberman, and Saldana framework data condensation, data display, and conclusion drawing while data validity was ensured through source triangulation and member checking. The findings reveal that musyrif play a strategic role in enhancing student discipline through four main functions: (1) conceptor, by initiating ideas and programs such as diniyah activities after Isya prayer; (2) mediator and facilitator, bridging students, parents, and the institution; (3) innovator and creator, by designing creative activities to foster discipline; and (4) policy maker, by formulating and enforcing integrated regulations between the ma’had and the madrasah. These roles contribute to the creation of a conducive, orderly, and disciplined learning environment. This study offers practical insights for Islamic boarding schools in optimizing the role of musyrif as key agents in shaping student discipline. It also contributes theoretically by highlighting the managerial and instructional dimensions of musyrif roles, an aspect less explored in previous studies.